Group of pregnant and pregnant couples: strengthening the humanization of childbirth and birth (Research, Society and Development, 2021)
Objective: To identify the contribution of a group of pregnant women and pregnant couples to consolidate the principle of humanization of childbirth and birth, in the perception of women and their companions. Method: descriptive and exploratory qualitative research. Data collection was performed through interviews from August 2018 to March 2019. The analysis was carried out qualitatively, according to the operative proposal of Minayo. Results: The health education activities carried out in the group contribute to the promotion and protection of childbirth as a healthy and physiological process, prepare women for decision making and empower women for possible childbirth. Final considerations: The Group of Pregnant Women and pregnant couples has contributed to the humanization of childbirth and birth care, providing a pleasant experience for the participants.